THE INFLUENCE OF LEADERSHIP ON THE IMPLEMENTATION OF STRATEGIC HUMAN RESOURCE MANAGEMENT: A STUDY FROM A COMMERCIAL PERSPECTIVE - Pereira da Silva Leão, Airton; Borges Alves Pessoa, Solange; Guimarães Bezerra, Thayná; Pereira Staiger, Ronnyere; Silva Gomes, Randal; Rurik Aparecido Gomes, Bernardo; Xavier de Melo, Ramon; Carneiro dos Santos, Ronebes; Melo Costa Simões, Valéria (Revista Gênero e Interdisciplinaridade, 2026)
Strategic people management is the subject of extensive research that emphasizes the relationship between management policies and practices and other organizational variables. Organizational actors have little role in management, making the process of implementing people management little explored, having said that, the focus on leadership enters, being a process of influence in the field of strategic management, because it is associated with dynamicity by facilitating communication between managers and employees. From this context, this article intends to discuss the importance of leadership in the strategic management of organizations, with the aim of responding to the following problem: what is the role of leadership in the strategic management of people from a commercial point of view? This is a literature review, exploratory character, qualitative approach. The databases used were Digital Library of Dissertations (BDTD), Google Scholar and the scientific electronic library online (SciELO) website cos descriptors administration, strategic management, organizations, leadership and sales, including original articles, dissertations, course completion papers, monographs, theses of the period 2017-2022. The 14 articles elucidated that leadership in the market sector is all about breaking with traditional models and challenging accepted industry conventions, influencing strategic management. because leadership within an organization needs to demonstrate the elements of creativity, intuition, authenticity, determination, boldness, focus on results and long-term vision that cannot be achieved through traditional reward systems and comprehensive performance tools. It is concluded that leadership plays a fundamental role in strategic management and is tied to attributes such as creativity, assertive communication and responsibility, helping GE to achieve its objectives efficiently, even in the face of mishaps such as market changes. Thus, GE continues to be a set of practices aimed at achieving business strengthening.